2015
DOI: 10.1108/s1074-754020150000017014
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Contribution of Start-Up Firms in Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The share of surviving entrants was highest in cohort 2005 (58.3%) and lowest in cohort 2002 (54.3%). These numbers are comparable to the ones reported in Schneck and May-Strobl (2015), who analyzed microenterprises. Firms of cohort 2001 exhibit a higher survival rate than the new firms of cohorts 2002 to 2008, which is due to the share of established firms in this particular cohort.…”
Section: Variablessupporting
confidence: 90%
“…The share of surviving entrants was highest in cohort 2005 (58.3%) and lowest in cohort 2002 (54.3%). These numbers are comparable to the ones reported in Schneck and May-Strobl (2015), who analyzed microenterprises. Firms of cohort 2001 exhibit a higher survival rate than the new firms of cohorts 2002 to 2008, which is due to the share of established firms in this particular cohort.…”
Section: Variablessupporting
confidence: 90%
“…According to Malik (2013), between 2007 and 2011, London's economy grew about 12.5% more than the rest of the country with the installation of a startup incubator. Schneck and May-Strobl (2015) demonstrated that 6.5% of sales in Germany originate from nascent companies. Sabella, Farraj, Burbar, and Qaimary (2014) state that the adoption of a policy of greater incentive to entrepreneurship and, consequently, of incentives to startups, increased the Gross Domestic Product (GDP) of Palestine by 7.33% when compared to previous years.…”
Section: Literature Reviewmentioning
confidence: 99%